The Role of Digital Transformation to Economic Growth in the Provinces of South Sumatra, Aceh, and Lampung - Wardhono, Adhitya; Yaqin, Misbahol; Sari, Mega Indah; Sari, Kiky Indah; Qori’ah, Ciplis Gema; Nasir, M. Abd. (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2023)
The development of digital transformation is critical for innovation and surviving the crisis and being a sustainable focus. This study aims to observe the relationship between digital transformation and selected macroeconomic variables in accelerating economic growth recovery at the regional level. The data used is panel data from 2018Q1 - 2020Q4 in three Sumatra provinces, namely South Sumatra, Aceh, and Lampung. The method used is Panel Vector Autoregression (PVAR). The results of this study confirm that internet uses and investment contribute to economic growth in three Sumatra provinces. From these results is recommended that the government need to develop digital access and understanding such as internet use in the three provinces of Sumatra, namely South Sumatra, Aceh and Lampung. This is in order to maximize the potential of existing economic growth.